2015
DOI: 10.1104/pp.15.00871
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Future: Effects of Short-Term Climate Extremes on Isoprene-Emitting and Nonemitting Poplar

Abstract: (H.R.); 0000-0002-9825-867X (J.-P.S.).Isoprene emissions from poplar (Populus spp.) plantations can influence atmospheric chemistry and regional climate. These emissions respond strongly to temperature, [CO 2 ], and drought, but the superimposed effect of these three climate change factors are, for the most part, unknown. Performing predicted climate change scenario simulations (periodic and chronic heat and drought spells [HDSs] applied under elevated [CO 2 ]), we analyzed volatile organic compound emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 111 publications
(135 reference statements)
3
56
0
Order By: Relevance
“…The accumulation and compartmentation of some metabolites (expecially of ROS scavengers and of compatible solutes such as proline, betain or glycinebetaine which are also important for osmoregulation) help to protect cells from damages caused by heat or drought and to maintain basic cellular functions (Hormaetxe et al, 2007;Wang et al, 2010;Albert et al, 2012;Hu et al, 2013;Wujeska et al, 2013: AbdElgawad et al, 2015Grant et al, 2015). Such protective effects were recently reported in detail for phenolic compounds (Farfan-Vignolo and Asard, 2012;Wegener et al, 2015), α-tocopherol (MunneBosch and Alegre, 2000; Farfan-Vignolo and Asard, 2012) and for isoprene production/emission (Velikova et al, 2005 ;Velikova, 2008;Centritto et al, 2014 ;Seco et al, 2015 ;Vanzo et al, 2015). Advantages of drought acclimation for improved plant performance were reported by Selote et al (2004).…”
Section: Reactive Oxygen Species and Protection Of Chloroplast Constimentioning
confidence: 74%
“…The accumulation and compartmentation of some metabolites (expecially of ROS scavengers and of compatible solutes such as proline, betain or glycinebetaine which are also important for osmoregulation) help to protect cells from damages caused by heat or drought and to maintain basic cellular functions (Hormaetxe et al, 2007;Wang et al, 2010;Albert et al, 2012;Hu et al, 2013;Wujeska et al, 2013: AbdElgawad et al, 2015Grant et al, 2015). Such protective effects were recently reported in detail for phenolic compounds (Farfan-Vignolo and Asard, 2012;Wegener et al, 2015), α-tocopherol (MunneBosch and Alegre, 2000; Farfan-Vignolo and Asard, 2012) and for isoprene production/emission (Velikova et al, 2005 ;Velikova, 2008;Centritto et al, 2014 ;Seco et al, 2015 ;Vanzo et al, 2015). Advantages of drought acclimation for improved plant performance were reported by Selote et al (2004).…”
Section: Reactive Oxygen Species and Protection Of Chloroplast Constimentioning
confidence: 74%
“…In addition, within the suit of measured volatiles we found no indication for other compounds, which should co-occur with such C5-volatiles (e.g., C6 leaf alcohols or acetaldehyde). In a similar study the absence of those compounds during a heat-drought wave was attributed to natural drought progression not being comparable to fast drying after artificial cutting (Vanzo et al, 2015).…”
Section: Volatile Organic Compoundsmentioning
confidence: 79%
“…After periods of drought stress, a quick recovery of isoprene emissions seems to emerge as a common feature that has also been observed in previous studies (Sharkey and Loreto, 1993;Pegoraro et al, 2004b;Velikova and Loreto, 2005;Brilli et al, 2013) and may help isoprene emitting plants to cope with abrupt and repeated temperature changes as commonly observed under natural conditions. However, studies on isoprene dynamics following stress release are scarce and there is to our knowledge only one study that considers dynamics of isoprene emissions during and following prolonged combined heatdrought stress (Vanzo et al, 2015). Vanzo et al (2015) found that isoprene-emitting poplars recovered rapidly from stress and even increased photosynthesis during recovery in contrast to nonisoprene-emitting trees, which showed weaker recovery of photosynthesis.…”
Section: Stress Response and Recoverymentioning
confidence: 99%
See 2 more Smart Citations